Development of Sterilisation Procedures and in Vitro Studies of Nymphaea lotus - Sulaiman, Elixon Sunian (2004)
Water lilies (Nymphaea sp.) are one of the most valuable aquatic ornamental plants which have a bright potential to be a multimillion-dollar commodity in the floriculture trade. They could be exploited as cut flowers (Master, 1974), ornamental plants for water garden, urban landscape for aquascaping and restoration projects (Kane and Philman, 1992) and sources for pharmaceutical and cosmetic products (Perry, 1987). Water lily family consists of approximately 50-60 species found in tropical to cold temperate region (Halijah, 2000). Flowers of water lilies are available in many colours including red, pink, yellow and white. Water lilies are not only beautiful but they are also useful in creating a balanced environment in ponds or lakes as well as improving the water quality. They function as surface vegetation in controlling the amount of direct sunlight that penetrates the water surface, thus, stabilising the water temperature particularly during dry season, and also control the algal growth from over blooming which causes the green water problem (Dawes, 1989). In Putrajaya Wetland Garden in Malaysia, water lilies are planted in open water as ornamental plants (Radiah, 2000). Many years ago, Europeans, Asians and Africans consumed the seeds and tubers of water lilies as food in time of emergency. Nymphaea alba at one time was used by the French in the preparation of beer, while Irish and Scottish highlanders used it as a source of dye for dyeing wool (Perry, 1971). During the Egyptian civilization (approximately 4000 B.C), water lilies were used in religious ceremonies (Perry, 1987). Conventionally, water lilies are propagated vegetatively through tuber production or from new plants sprouting from the underground rhizomatous stem. However, such propagation methods are restricted due to the slow and limited number of plants produced, diseases, large propagation space needed and an extended period to produce saleable plants. These factors contribute to a high production cost (Kelly and Fret, 1986) and often prevent an efficient and rapid production of planting materials to meet the market demand (Kane, 1991).